Ammonium Persulfate-Induced Graft Copolymer Based on Carboxymethyl Cellulose-g-PMAAm-co-PNIPAAm - Soleimani, Fatemeh; Sadeghi, Hossein; Shahsavari, Hadis; Soleimani, Arezou; Sadeghi, Fatemeh (Asian Journal of Chemistry, 2013)
In this study, a novel graft copolymer based on sodium carboxymethyl celloluse via a free radical polymerization method is synthesized. The graft copolymerization reaction was carried out in a homogeneous medium and by reaction of N-isopropylacrylamide and methacrylamide with carboxymethyl cellulose backbones. Evidence of grafting was obtained by comparing FTIR and TGA analysis of carboxymethyl cellulose and the graft copolymer as well as solubility characteristics of the products.